Pengaruh Modal Kerja, Volume Penjualan dan Biaya Operasional terhadap Laba Bersih pada Perusahaan Subsektor Semen yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Nur Hidayati (Universitas Batanghari Jambi, 2021)
The purpose of this research is to determine the effect of working capital, sales volume and operating expense simultaneously and partially on net profit in the cement subsector companies listed on the Indonesia Stock Exchange for the period 2015-2019. This research method is descriptive and quantitative method. This study uses secondary data. The analysis method used in this study was multiple linear regression with panel data using SPSS 22. tests conducted are normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, F test hypotheses, t test hypotheses and determine what coefficients of determination (R2).In this study, based on the sampling criteria, there are 4 companies that are sampled, namely PT. Indocement Tunggal Prakasa Tbk, PT. Semen Baturaja (Persero) Tbk, PT. Semen Indonesia (Persero) Tbk and PT. Wijaya Karya Beton Tbk. In accordance with the results of the study, spss 22 results obtained multiple linear regression equations namely Y = -2,830 + 0,470 +1,079 – 0,285 + e. So based on hypothesis testing, simultaneously (test F) working capital, sales volume and operating expense significantly affect net profit because the value of Fcount is greater than Ftable (29,641 > 3,24). Partially (test t) working capital significantly affects net profit because the tcount value is greater than ttable (2,323 > 2,120), sales volume has a significant effect on net profit because the tcount value is greater than ttable (4,599 > 2,120) and operating expenses had no significant impact on net profit as the tcount value was smaller than ttable (1,376 < 2,120). From the results of this study, it can be concluded that working capital, sales volume and operating expense simultaneously have a significant impact on net income. Partially indicates that working capital has a significant effect on net income, sales volume has a significant effect on net income and operating expense have no significant effect on net income.